(3GdOGNdj(B-(3GdMchej(B-(3GdGOGQj (B-(3GdNGU(B-(3GdHjFj(B-(3GdefTBJ GdUZjQIs - (3CMeO Mdej(B, (3LeYIs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2009)
(3JWhQ eYGjjQ GdJObjb GdOGNdj GdOhdjI(B- (3JWhQ eYGjjQ GdJObjb GdMchej(B- (3JWhQ eYGjjQ GdJObjb GdEOGQj(B- (3JWhQ JObjb GdefTBJ GdNGUI(B- (3JWhQ eYGjjQ GdJObjb GdHjFj(B- (3JWhQ eYGjjQ JObjb GdefTBJ GdUZjQIs
(3eQGLY (B: (3dcd aUd eQLY ; GbJfj (B5 (3fSN SfI (B2010s
Keywords: (3GdJObjbs; (3GdeMGSHIs; (3GdeMGSHI GdMchejIs; (3JObjb GdMSGHGJs